The Pathological Chabges of Male Goat Infected by Haemonclus contortus (Rudolphi, 1803) - Estuningsih S.; Retnani E.B.; Esfandiari A. (Media Veteriner, 1996)
Pathological aspects of abomasum, intestine, liver, spleen, heart , bone marrow and lymphnode caused by H. contortus were examined. Twelve bucks. six to eight month of ages were divided into 4 groups. which were infected by 0 (DO). 200 (D200). 400 (D400). and 600 (D600) h r d stage larvae of H. contortus. Larvae was administered orally 3 times a week for 8 weeks. Patological aspects including macro and microscopic findings were studied for enteritis, abomasitis, extramedullary haemopoietic centre forming, germinal centre activity of spleen and lymphnode and activity of bone marrow.